Counterproductive Work Behaviors to Cope With Person-Organization Misfit - Kinard, Brian R.; Chakrabarty, Subhra (Journal of Organizational Psychology, 2024)
A random sample of employees was surveyed to explore the effect of person-organization fit on counterproductive work behaviors. There was a significant negative relationship between person-organization fit and counterproductive work behaviors. A lack of person-organization fit may be construed by employees as a depletion of psychological resource. As the conservation of resources theory (Hofboll, 1989) argues, it appears that employees may have replenished the loss of this psychological resource (person-organization fit) by engaging in counterproductive work behaviors. Consequently, organizations should assess the person-organization fit of all employees and prevent the negative consequences of counterproductive work behaviors. The findings have several implications for practitioners.